Sustainable production of reduced graphene oxide using elemental sulfur for multifunctional composites - Nam, Ki-Ho; Kim, Kyeongmin; Kim, Seo Gyun; Lee, Heon Sang; Jung, Hana; Yu, Jaesang; Jang, Se Gyu; Ku, Bon-Cheol; Moon, Bongjin; You, Nam -Ho (ELSEVIER SCI LTD, 2019)
We herein report on a green, facile, and sustainable production of sulfur-doped reduced graphene oxide (S-RGO) and their use in mechanically strong gas barrier polymers. S-RGO was successfully obtained by directly utilizing elemental sulfur in the absence of any organic solvent or catalyst. This method suggests that the sulfur treatment of GO causes the insertion of a variety of sulfur forms such as thiol, thioether, sulfoxide, sulfone, and sulfonic acid at the platelet edges or surfaces. It also restores graphitic networks on the basal planes, enabling easy exfoliation in liquid phases. The resultant S-RGO is highly dispersible in organic solvents and exhibits a high C/O ratio (13.2), excellent electrical conductivity (179 S cm(-1)), and a high Hg removal capacity. The molecular dynamics (MD) simulation supports the discussion on the interfacial mechanics for the solvent-exfoliation of S-RGO. The S-RGO can significantly improve the tensile strength (255 MPa) and Young's modulus (6.2 GPa) of the host polyimide, (PI) even with a 0.5 wt% filler loading. Furthermore, loading S-RGO as a filler in PI films can lead to an exceptional oxygen gas barrier performance, resulting in an approximately 95% reduction (at 3 wt%) compared with that of a pristine PI film. This strategy provides a new, environmentally friendly, and cost-effective reduction methodology for synthesizing high-quality and multifunctional RGOs and their nanocomposites.
Keywords: MECHANICAL-PROPERTIES; EFFICIENT REMOVAL; GRAPHITE OXIDE; OXYGEN-BARRIER; GAS BARRIER; REDUCTION; NANOCOMPOSITES; NANOPARTICLES; NANOCRYSTALS; CHEMISTRY